3p25.3 microdeletion of GABA transporters SLC6A1 and SLC6A11 results in intellectual disability, epilepsy and stereotypic behavior. Issue 12 (24th September 2014) - Dikow, Nicola; Maas, Bianca; Karch, Stephanie; Granzow, Martin; Janssen, Johannes W.G.; Jauch, Anna; Hinderhofer, Katrin; Sutter, Christian; Schubert‐Bast, Susanne; Anderlid, Britt Marie; Dallapiccola, Bruno; Van der Aa, Nathalie; et al.
<x xml:space="preserve">Abstract</x> Small interstitial deletions affecting chromosome region 3p25.3 have been reported in only five patients so far, four of them with overlapping telomeric microdeletions 3p25.3 and variable features of 3p‐ syndrome, and one patient with a small proximal microdeletion and a distinct phenotype with intellectual disability (ID) and multiple congenital anomalies. Here we report on three novel patients with overlapping proximal microdeletions 3p25.3 of 1.1–1.5 Mb in size showing a consistent non‐3p‐ phenotype with ID, epilepsy/EEG abnormalities, poor speech, ataxia and stereotypic hand movements. The smallest region of overlap contains two genes encoding sodium‐ and chloride‐dependent GABA transporters which have not been associated with this disease phenotype in humans so far. The protein function, the phenotype in transporter deficient animal models and the effects of specific pharmacological transporter inhibition in mice and humans provide evidence that these GABA transporters are plausible candidates for seizures/EEG abnormalities, ataxia and ID in this novel group of patients. A fourth novel patient deleted for a 3.16 Mb region, both telomeric and centromeric to 3p25.3, confirms that the telomeric segment is critical for the 3p‐ syndrome phenotype. Finally, a region of 643 kb is suggested to harbor one or more genes causative for polydactyly which is part of the 3p‐ syndrome. © 2014 Wiley Periodicals, Inc.